2017
DOI: 10.1016/j.bbi.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-modulator inter-alpha inhibitor proteins ameliorate complex auditory processing deficits in rats with neonatal hypoxic-ischemic brain injury

Abstract: Hypoxic-ischemic (HI) brain injury is recognized as a significant problem in the perinatal period, contributing to life-long language-learning and other cognitive impairments. Central auditory processing deficits are common in infants with hypoxic-ischemic encephalopathy and have been shown to predict language learning deficits in other at risk infant populations. Inter-alpha inhibitor proteins (IAIPs) are a family of structurally related plasma proteins that modulate the systemic inflammatory response to infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 59 publications
3
35
2
Order By: Relevance
“…Recent work has also shown that exogenous treatment with IAIPs in neonates exposed to HI reduces neuronal cell death, improves neuronal plasticity, ameliorates complex auditory processing deficits, cognitive function, and behavioral outcomes (Gaudet et al, 2016; Threlkeld et al, 2014, 2017). Administration of urinary bikunin, the light chain of IAIPs demonstrated neuroprotective properties by reducing pro‐inflammatory mediators and resulting in milder ischemia related brain injury in young piglets (Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has also shown that exogenous treatment with IAIPs in neonates exposed to HI reduces neuronal cell death, improves neuronal plasticity, ameliorates complex auditory processing deficits, cognitive function, and behavioral outcomes (Gaudet et al, 2016; Threlkeld et al, 2014, 2017). Administration of urinary bikunin, the light chain of IAIPs demonstrated neuroprotective properties by reducing pro‐inflammatory mediators and resulting in milder ischemia related brain injury in young piglets (Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal brain injury is known to result in auditory deficits that contribute to language comprehension and learning difficulties [69,70]. Rats treated with IAIPs after neonatal HI, when tested as adults (23 weeks after injury), exhibited significantly better auditory discrimination capacity compared with untreated counterparts after injury [71]. These results demonstrate that short-term treatment with exogenous IAIPs after HI in neonatal subjects has the potential to provide cognitive improvements that persist into later life.…”
Section: Neurobehavioral Effectsmentioning
confidence: 73%
“…Future studies are required to determine whether the efficacy of treatment with IAIPs is sex-specific. Initial studies identifying neuroprotection by IAIPs in neonatal rodents exposed to HI investigated mainly male subjects [64,68,71]. More recent studies investigating both male and female subjects suggest that, although brain infarct volumes were reduced in both sexes after treatment with IAIPs given soon after HI [40,63], when treatment was delayed, males exhibited greater reductions in infarct volumes than female neonatal rodents [63].…”
Section: Sex-specific Efficacymentioning
confidence: 99%
“…This heavy chain-to-hyaluronan interaction is facilitated by Tumor necrosis factor-inducible gene 6 (TSG-6) and is currently the only known interaction of the ITI heavy chain [ 60 ], serving to cross-link molecules within the ECM and enhance ECM rigidity [ 61 ]. ITIH-family proteins have been revealed to modulate peripheral inflammatory responses in multiple diseases [ 62 ]. The formation of extracellular or cell surface ITIH-HA complexes promotes the adhesion of leukocytes [ 60 ].…”
Section: Discussionmentioning
confidence: 99%